Hemorrhagic cystitis: A challenge to the urologist - R Manikandan (Indian Journal of Urology, 2010)
Severe hemorrhagic cystitis often arises from anticancer chemotherapy or radiotherapy for pelvic malignancies. Infectious etiologies are less common causes except in immunocompromised hosts. These cases can be challenging problems for the urologist and a source of substantial morbidity and sometimes mortality for the patients. A variety of modalities of treatment have been described for the management of hemorrhagic cystitis but there is none that is uniformly effective. Some progress has been made in the understanding and management of viral hemorrhagic cystitis. This article reviews the common causes of severe hemorrhagic cystitis and the currently available management options.